Réaction de deux espèces d’igname (Dioscorea spp.) traitées avec du vin de palme (Elaeis guineensis Jacq.), aux champignons responsables des pourritures d’igname - Assiri, Patrice Kouamé; Diallo, Attaky Hortense; Tschannen, Andres; Ake, Severin (Afrika Focus, 2009)
The sensitivity of Dioscorea alata var. bètè-bètè and D. cayenensis-rotundata var. krenglè treated with palm wine obtained from oil palm trees (Elaeis guineensis Jacq.) to seven fungi isolated from yam rots was assessed. Yam tubers were collected from two markets in Abidjan and also from storage sites in Bringakro (at 180 km from Abidjan, Côte d’Ivoire). Pathogenecity tests showed that Penicilium oxalicum was the most pathogenic among all fungi isolated. Krenglè was more susceptible than bètè-bètè. In vitro, fermented palm wine totally inhibited mycelial growth of all fungi isolated with the exception of P. oxalicum and Aspergillus niger. Inhibition percentage of mycelial growth of all fungi was more important for krenglè than bètè-bètè. Regardless the yam species, in vivo tests showed that fermented palm wine was more effective than non fermented palm wines when used as a preventive treatment. Key words: natural fungicide, palm wine, integrated disease management